The Border: A Space of Life for Migrants and Refugees - Delia Dutra; Tuíla Botega (Gender a Výzkum, 2019)
In 2017 the Scalabrinian Centre for Migration Studies (CSEM) started a comprehensive programme of research entitled ‘Rebuilding Life in the Border: Assistance and Protection to Migrants and Refugees’.